PREVALENSI HIPERTENSI DAN KEBIASAAN MEROKOK, KONSUMSI ALKOHOL, SERTA KONSUMSI GARAM PADA PENDUDUK USIA 20-59 TAHUN DI WILAYAH KERJA UPTD PUSKESMAS KUBU II - Uttari Priyadarshini (Intisari Sains Medis, 2015)
From the report of UPTD Puskesmas Kubu II in 2012, hypertension was one of the tenmost frequent illnesses in their working area. Hypertension is connected with smoking habit, alcohol and salt consumption. The purpose of this study is to describe the prevalence of hypertension and smoking habit, consumption of alcohol and salt among the villagers in the working area of UPTD Puskesmas Kubu II. This research was conducted in August 2012 atworking area of UPTD Puskesmas Kubu II with a cross-sectional study design which was participated by 80 samples within 20-59 years old. Data were collected directly using an anthropometric measurements, blood pressure measurement and questionnaires. The result showed that hypertension tends to affect villagers who drinkalcohol â‰¥ 7 times per week and smoke>20ciggarettes per day. We may conclude that the prevalence of hypertension among villagersinworking area of UPTD Puskesmas Kubu IIis quite high. There are also tendencies of bad habit regarding risk factor of hypertension. This requires further attention.